2002
DOI: 10.1046/j.1469-0705.2002.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal duodenal obstructions: increased risk of prenatal sudden death

Abstract: The present study indicates that duodenal obstruction is a more serious condition than previously believed, with an increased risk of prenatal asphyxia and death, even when the karyotype is normal and no associated anomalies are present. We consider the possibility that it could be caused by bradycardia/asystole following vagal overactivity due to distension of the upper gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
1
32
1
Order By: Relevance
“…This finding supports the hypothesis that bile acid toxicity may have caused umbilical cord ulceration. Duodenal atresia is strongly associated with chromosomal abnormalities, mainly with the risk of trisomy 21 [1,2] . Eighteen cases of umbilical cord ulceration with duodenal and jejunoileal atresia were previously reported [3-9, 13, 14] and 12 of these 18 cases were confirmed by karyotyping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding supports the hypothesis that bile acid toxicity may have caused umbilical cord ulceration. Duodenal atresia is strongly associated with chromosomal abnormalities, mainly with the risk of trisomy 21 [1,2] . Eighteen cases of umbilical cord ulceration with duodenal and jejunoileal atresia were previously reported [3-9, 13, 14] and 12 of these 18 cases were confirmed by karyotyping.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of duodenal atresia is 1-10/100,000 live births [1,2] . The lesion may be diagnosed prenatally by identifying the 'double bubble' sonographic sign.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hyperdistended uterus predisposes preterm delivery [17][18][19] ; reduced intake of amniotic proteins by the foetus with a bowel obstruction may be responsible for poor intrauterine growth. A recent paper by Brantberg et al [20] highlights the possibility that foetuses with CDO could have an increased risk of sudden intrauterine death due to bradycardia-asystolia secondary to vagal overactivity, triggered by a distended upper gastrointestinal tract. Some cases of severe foetal haemorrhage associated with intestinal obstruction and hydramnios have also been reported [21] .…”
Section: Discussionmentioning
confidence: 99%
“…A Norwegian study showed an increased risk of sudden, unexplained death in fetuses with small intestinal obstruction (14). Bradycardia episodes were recorded prior to fetal death and were interpreted as resulting from vagal overactivity associated with distension of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%